1986
DOI: 10.1056/nejm198608073150601
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Kawasaki Syndrome with Intravenous Gamma Globulin

Abstract: We compared the efficacy of intravenous gamma globulin plus aspirin with that of aspirin alone in reducing the frequency of coronary-artery abnormalities in children with acute Kawasaki syndrome in a multicenter, randomized trial. Children randomly assigned to the gamma globulin group received intravenous gamma globulin, 400 mg per kilogram of body weight per day, for four consecutive days; both treatment groups received aspirin, 100 mg per kilogram per day, through the 14th day of illness, then 3 to 5 mg per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
608
4
16

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,293 publications
(646 citation statements)
references
References 11 publications
6
608
4
16
Order By: Relevance
“…However, administration of IVIg reduces coronary artery abnormalities such as aneurisms from 20% to 25% to 3% to 5% within 10 days of illness onset. 43 Recently, Lin et al 44 highlighted the role of HLA-E in the pathogenesis of KD. They measured plasma concentrations of soluble HLA-E (sHLA-E) by enzyme-linked immunosorbent assay in 96 Taiwanese patients with KD and in 93 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, administration of IVIg reduces coronary artery abnormalities such as aneurisms from 20% to 25% to 3% to 5% within 10 days of illness onset. 43 Recently, Lin et al 44 highlighted the role of HLA-E in the pathogenesis of KD. They measured plasma concentrations of soluble HLA-E (sHLA-E) by enzyme-linked immunosorbent assay in 96 Taiwanese patients with KD and in 93 healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…myasthenia gravis, and Kawasaki disease (16)(17)(18)(19). In this rcport, we describe the beneficial effccts of IV gamma globulin therapy on the clinical and laboratory features of systemic JRA.…”
mentioning
confidence: 99%
“…IVIG has now been proven to be efficacious for Kawasaki disease, idiopathic thrombocytopenic purpura, and polymyositisdermatomyositis. 7,8,22 The benefits seen in Kawasaki disease are particularly relevant to ARF, because the incidence of coronary artery aneurysms is significantly reduced by IVIG administration. A large variety of immunological mechanisms may be involved in the pathogenesis of ARF, including cross-reactive antibodies, release of cytokines, activation of T and B cells, and immune complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has indicated that intravenous immunoglobulin (IVIG) may be of benefit in immune-mediated cardiac disorders. 7,8 This is seen particularly in Kawasaki disease, in which the use of high-dose IVIG markedly reduces the prevalence of coronary artery abnormalities. 9 We present the results of a randomized, placebo-controlled trial of IVIG as an acute intervention in patients with ARF to determine whether there was a reduction in the extent and severity of carditis, more rapid resolution of inflammatory activity, or decreased chronic morbidity.…”
mentioning
confidence: 99%